PENGARUH RESILIENSI MATEMATIS DAN LINGKUNGAN BELAJAR TERHADAP HASIL BELAJAR MATEMATIKA SISWA SMP - Nur Hadra, Putri; Azainil; Fendiyanto, Petrus (Prismatika: Jurnal Pendidikan dan Riset Matematika, 2024)
This study is an ex post facto research aimed at determining the influence of m|athem|atic|al resilience |and le|arning environment on the m|athem|atics le|arning outcomes of students |at SMP Negeri 29 S|am|arind|a for the |ac|ademic ye|ar 2023/2024. In this study, there |are two independent v|ari|ables, n|amely m|athem|atic|al resilience |and le|arning environment, |and one dependent v|ari|able, which is m|athem|atics le|arning outcomes. The popul|ation of this study consists of |all eight-gr|ade students |at SMP Negeri 29 S|am|arind|a for the |ac|ademic ye|ar 2023/2024. S|ampling w|as done using |a prob|ability s|ampling technique with |a tot|al s|ample size of 163 students. The rese|arch instruments used were questionn|aires for m|athem|atic|al resilience |and le|arning environment, |and |a le|arning outcomes test. The d|at|a |an|alysis used in this study includes descriptive statistics and inferential statistics in the form of multiple linear regression analysis. The results of the descriptive analysis show that the average score for the mathematical resilience questionnaire falls within the moderate category with a percentage of 36.2%. The average score for the learning environment questionnaire also falls within the moderate category with a percentage of 37.4%. Additionally, the average mathematics learning outcomes are in the moderate category with a percentage of 41.4%. The results of inferential analysis indicate that mathematical resilience and learning environment have an influence on the mathematics learning outcomes of eighth-grade students at SMP Negeri 29 Samarinda for the academic year 2023/2024.